Association of MRI T1 and T2 grayscale values and Sieper/Rudwaleit score with disease activity and progression in ankylosing spondylitis - Dang, Wantai; Zheng, Xinru; Muñoz, Luis E.; Muñoz-Becerra, Marco; Xu, Dan; Herrmann, Martin (International journal of rheumatic diseases, 2025)
Objective This study aimed to investigate the relationship between MRI T1 and T2 grayscale values and Sieper/Rudwaleit score with disease activity and inflammation levels in patients with ankylosing spondylitis (AS). Methods Totally, 174 AS patients and 41 healthy controls were enrolled and received MRI and computed tomography (CT) of sacroiliac joints (SIJ). Results Sieper/Rudwaleit score positively related to CT grade (p = 0.038). MRI T1 values correlated negatively and positively to MRI T2 values (p = 0.001) and CT grade (p = 0.016), respectively. According to multiple linear regression analysis, Sieper/Rudwaleit score showed an independent positive correlation with bone marrow fat deposition and Bath ankylosing spondylitis disease activity index (BASDAI) (both p < 0.001). MRI T1 values exhibited an independent positive correlation with male sex, duration of AS, and BASDAI; while they inversely related to C-reactive protein (CRP), platelets, albumin, and creatinine (all p < 0.05). MRI T2 values exhibited an independent positive correlation with CRP and neutrophils, and a negative correlation to age, male sex, and creatinine (all p < 0.05). CT grade disclosed an independent positive relationship with human leukocyte antigen B27 positivity, duration of AS, ankylosing spondylitis disease activity score, CRP, platelets, and alkaline phosphatase (all p < 0.05). Conclusion MRI T1 and T2 values combined with the Sieper/Rudwaleit score may serve as potential biomarkers for evaluating inflammatory activity and disease progression in AS. CT serves as an adjunct to MRI to monitor the activity of AS.
Erstmals veröffentlicht: 18. Juli 2025
Gesehen am 28.08.2025